Generic Drugs: The Evolving Landscape and the Mentalities - Lacasse, Francois-Xavier (Pharmaceutical Research - Recent Advances and Trends Vol. 3, 2024)
The present study discusses the expense associated with development, by narrowing the cost of development (raw materials) and workforce for generic drugs. During the last decade, the generic landscape has considerably evolved. The last two waves of several MM$ of off-patented drugs may be held responsible for this change. For example, the amount of money generated by statins, the proton pump inhibitors (PPIs), according to several experts, may now be difficult to reproduce. However, things cannot be seen from a monolithic way of thinking but should be foreseen with a holistic approach. The cost of generic medications is continuously declining. It is paradoxical because government organizations are raising their expectations for quality at the same time, driving up the cost of development. Furthermore, in December 2016, the FDA released revision 2 [1] of their Refuse to Receive Standards, for ANDA Submissions. After discussion with several experts who have attended numerous meetings on the topic with the FDA, data quality and regulatory operations were at the heart of this new guidance. Additionally, the generic market is facing the challenge that it will have to change its vision if it wants to survive, biologics getting more and more popular and cannot be “genericized” per se, but will become biosimilar, or second-entry biologics. This assumption is confirmed by looking at the contract research organization where the number of bioequivalence studies has been going down over the last decade. Therefore, generics will have to think outside of the box, and to date, the best compromise seems to develop new routes of administration and or new formulations of an already marketed drug substance. This short communication will illustrate a way of thinking and a summary of the generic landscape that is evolving.